Job training and its impact on some biochemical variables and achievement of the weight-motivated person (Journal of the College of Basic Education, 2022)
The study aimed to:1- Preparing (functional strength) exercises that suit the capabilities of the research sample.2- Identify the effect of functional strength training on some biomechanical variables for weight players. The researcher used the experimental method for its suitability in solving the research problem and reaching the achievement of its objectives, as the researcher used the design of one experimental group. This design includes conducting the experiment on one group as it is subjected to a pre-measurement, then the experimental variables whose effect is to be tested are then entered into a dimensional measurement, and the research sample included The national team players totaling (2) players. The researcher used some biochemical variables and achievement to obtain results that support the research work.